This Study Examined the Social Factors Affecting Educational Failure Girl Faculty of Humanities PNU of Ahwaz - bahram nikbakhsh (توسعه اجتماعی)
Nowadays, education is undoubtedly the most important factor of cultural, social and economic development of a society. Therefore, most societies try their best in defining and adopting their educational goals and methods. Obviously, such matter requires extensive, comprehensive and accounted planning with regards to general and educational goals of any society. But, what the educational goals in courses of education are and how appropriate the methods for achieving those goals are is still an open question for beneficiaries of educational system in any society. Educational failure is one of the biggest adversities of education in any system, wasting large amounts of facilities, resources, human talent and economic potentialsand causing irreversible effects on individual and social dimensions. In this project, we intend to study and analyze educational failure as a social problem and dilemma. With regards to the proportion, cluster sample is used in this study and 150 people participated through questionnaires. After accumulation of data using SPSS software, the data then was analyzed in two descriptive and inferential levels, and all assumptions of this study are confirmed through this level of analysis. As a result of this study, the more family tension and conflicts are, and the less students study during terms, consequently, the possibility of educational failure is going to be higher. Correlation of mixed gender classes and educational failure variants is very low. Finally, some solutions and suggestions are provided regarding the results of this study.